Posttraumatic growth in people living with HIV : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Wellington, New Zealand - Chi, Danni (Massey University, 2020)
Nowadays, HIV is no longer necessarily terminal but remains a chronic and stigmatising illness. People living with HIV may experience posttraumatic growth (PTG) through processing HIV diagnosis and its associated issues. Two studies were conducted to investigate the processes of PTG among people living with HIV in New Zealand (NZ). Study 1 was quantitative and conducted among 77 people with HIV. It examined the relationships between PTG and its potential correlates: demographics, event centrality, deliberate rumination, active and avoidance coping, sense of coherence, optimism, instrumental and emotional support, posttraumatic stress symptoms (PTSSs), and perceived mental and physical health. Study 1 found the relationship between event centrality and PTG was sequentially mediated by deliberate rumination and avoidance coping, and this relationship was enhanced by higher levels of sense of coherence, optimism, and emotional support. Higher levels of PTG were associated with more positive perceptions of physical health in participants who had lived with HIV longer, but not PTSSs or perceived mental health. Study 2 comprised semi-structured interviews with 16 participants which were analysed using thematic analysis. Three themes were identified: challenges, event-related cognitive processing, and rebuilding of assumptions. The findings suggested that PTG might be related to perceived violations of beliefs and goals, coping with events, and rebuilding of assumptions. This process was found to be influenced by personal and social context (support and stigma). Participants who reported PTG could have been wiser but not necessarily happier. The findings of Studies 1 and 2 support current theories of PTG in general, provide a more in-depth picture of cognitive processing and PTG in participants with HIV, and highlight the importance of personal and social contexts in investigating the processes and implications of PTG. Future studies need to be aware that PTG may be a multidimensional construct, occurring on multiple levels.
Keywords: HIV-positive persons; New Zealand; Psychology; Attitudes; Posttraumatic growth; 520304 Health psychology